Fundamentals of Green Supply Chain Management: Organizational Measures on Implementation - Raju, Valliappan; Poh, Siew Phung; Kalimuthu, Ramanathan (International Journal of Supply Chain Management, 2019)
A coordinated effort among store network accomplices is fundamental to upgrade ecological execution amid the existence cycle of an item. Between hierarchical measures for green inventory network, management will in general show assorted examples in light of different prerequisites that develop in an unpredictable production network. In any case, this assorted variety hampers the extensive understanding and efficient selection of these measures. Consequently, this paper characterizes different between hierarchical measures for green production network the executives into a few coordinated effort designs and breaks down their auxiliary relations through an interpretive basic displaying. The outcomes uncover the joint effort designs that have higher driving force and reliance than different examples and, in this way, require further considerations.